Microstructures and Mechanical Properties of Al/Fe and Cu/Fe Joints by Continuous Drive Friction Welding - Yanni Wei; Fu Sun (Advances in Materials Science and Engineering)
The dissimilar pure metals Al/Fe and Cu/Fe with different metallurgical compatibility were joined by continuous drive friction welding. The friction weldability was investigated. The microstructure of the joining interface was analyzed by scanning electron microscopy, and the chemical compositions were tested by energy-dispersive spectroscopy. The joining strength was evaluated by tensile test, and the fracture was detected by X-ray diffraction analysis. The results show that sound joints of Al/Fe and Cu/Fe can be obtained by continuous drive friction welding process. A discontinuous reaction layer was formed on Al/Fe interface, and no obvious reaction layer appeared on Cu/Fe interface. The tensile strength of the joints increased with increasing friction pressure, and the highest strength could reach up to 70 MPa for Al/Fe joint and 222 MPa for Cu/Fe joint. All the Al/Fe friction-welded samples failed at the friction interface, while the Cu/Fe joint under 36 and 44 MPa friction pressure failed at Cu matrix during the tensile test.